Efektivitas Kebijakan Jaringan Utilitas Terpadu Dalam Penanganan Kabel Semrawut Untuk Menjamin Kenyamanan Masyarakat Di Kawasan Badung Selatan - I Nyoman Bagus Deva Prajina; Lilik Antarini; Komang Ema Marsitadewi (Policy and Maritime Review, 2024)
Problems related to messy cables occur because in tourist areas there are many facilities such as shops, hotels, boarding houses and so on. Increased population mobility will also affect, and there are still some providers who carry out their actions to install utility cables secretly without the knowledge and permission of the regional authorities. The government's efforts to handle and prevent messy cables are by accelerating infrastructure development and handling of messy cables in the Badung Regency area by establishing an Integrated Utilities Network Policy which is regulated in Badung Regency Regional Regulation No. 19 of 2016. This study aims to determine how the integrated utility network policy is in realizing community comfort in the South Badung area. This study uses a qualitative research approach method by examining primary and secondary data sources. The technique for determining informants in this study uses purposive sampling. This study uses the theory of policy effectiveness from Riant Nugroho. The results of the study indicate that the integrated utility network policy in realizing community comfort is quite good, which is based on the indicators of policy success that can be measured by the "five right" indicators, namely; right policy; right implementer; right target; right environment; and right process. But in its implementation, it is still not optimal, namely in the right target and right process indicators. There are several areas that have not all been realized through the integrated utility network policy due to several inhibiting factors such as uneven policy socialization and limited budget funds so that the implementation of the integrated utility network policy only focuses on several areas, namely the priority of tourism areas in the South Badung area as has been implemented in Seminyak Basangkasa Village and along Siligita Benoa Street.